The EFL Students’ Interaction Patterns in Online Learning Platforms: A Qualitative Observational Study - Mukmin, Moh. Fajar Amirul (LEOTECH: Journal of Learning Education and Technology, 2025)
This study explores EFL students’ interaction patterns in online learning platforms through a qualitative observational approach. Grounded in Moore’s interaction framework, the research focuses on three types of interaction: learner–teacher, learner–learner, and learner–content interaction. The study was conducted in an undergraduate online course involving 27 EFL students who participated in synchronous sessions supported by a learning management system. Data were collected through participant observation across five online meetings, supported by field notes, chat transcripts, and LMS discussion records. Thematic analysis was employed to identify recurring interaction behaviors and patterns. The findings reveal that learner–teacher interaction was the most dominant form, characterized by students’ responses to instructors’ questions and feedback. Learner–learner interaction occurred less frequently and was often limited to brief peer responses, while learner–content interaction varied depending on task requirements. These results indicate that although interaction is present in online learning environments, it is uneven and largely teacher-driven. The study highlights the importance of intentional instructional design and active facilitation to promote balanced interaction and meaningful engagement in online EFL learning contexts.